Alumni Perceptions On Aquascape Enterprise Training In Cirebon - Falatehan, A Faroby; Syaukat, Yusman; Bahtiar, Rizal (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2023)
The implementation of the Aquascape training is one of the activities of the IPB University's Dosen Pulang Kampung Program. This activity aims to enable ornamental fish cultivators to increase income through business diversification, namely making aquascapes. In order to know the impact of this activity, it is necessary to analyze the perceptions of the training alumni after the training activities took place. Based on the results of the Likert analysis, the training alumni highly agreed with this activity. The alumni stated that with this activity they would be able to increase their skills in making Aquascape, networks and income. The alumni of the training expected that the training will be held again with a longer time and more participants.